Distribution And Accumulation Of Heavy Metals In Fish in Cage System in Linggi Estuary, Malaysia - Yusof, Shahrizad (2005)
Kuala Linggi is developing into potential aquaculture area in the west coast of Peninsular Malaysia but this area is facing ecological pressures. In Malaysia, data on heavy metals in aquaculture area and the cultured organisms are lacking. This study is aimed to evaluate the metal levels in fish cage ecosystem and to investigate the exposure route of metals to the cultured fish. Samples of three different sizes of cultured Nile tilapia (Oreochromis niloticus), river sediment, cage sediment, river water and periphyton were analysed for Cu, Zn, Cd and Pb content using atomic absorption spectrophotometer. The cultured fish Hg content was also determined using mercury analyser. Heavy metals (Cu, Zn, Cd, Pb and Hg) are present in the aquaculture area in Linggi Estuary. Concentrations of Cu and Zn in the Linggi River water in the estuary are below the standards outlined by the Malaysian Department of Environment, but Cd and Pb concentrations are above the standards. Sediment Cu and Zn concentrations are at safe levels but Cd and Pb concentrations are above threshold levels. Sediment Cu and Zn are due to anthropogenic origin while large percentage of Cd and Pb in the sediment occurs naturally. There is a similar trend of Cu, Zn, Cd and Pb accumulation in three components of the aquaculture area environment, the periphyton, the cage sediment and the river sediment. This reflects close relationship of these components in cycling of the heavy metals. These three components, plus the commercial fish feed contribute heavy metals to the cultured fish. Different metals accumulate in different organs of the cultured fish. Copper is concentrated in the liver, Zn in the bone, Pb in the operculum, Cd in the gills and Hg in the kidney. Copper, Zn, Cd and Pb were also found to accumulate with age of fish. With respect to Cu, Zn and Hg, the fish cultured in Linggi Estuary is safe for consumption but their Cd and Pb levels are above the permissible level set by the Malaysian Government. Elevated levels of these of nonessential elements may pose threats to human health through consumption of the fish. These results indicate that some measures should be taken to prevent the contamination of the estuarine environment for human and animal health.